Implementation of School-Based Management in Improving the Quality of Education at MTs N 1 Padangsidimpuan - Marpaung, Wardatun Thaibah; Marpaung, Dian Pratiwi Br.; Nasution, Inom (IKAMAS: Manajemen Pendidikan Islam, 2023)
Abstract : In accordance with the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers Article 2 paragraph (1) confirms that teachers have a position as professionals at the level of basic education, secondary education, and early childhood education in the formal education pathway appointed in accordance with regulations legislation. Article 10 paragraph (1) states that "the competence of teachers as referred to in Article 8 includes pedagogic competence, personality competence, social competence, and professional competence obtained through professional education". Thus, it cannot be denied that teachers must have extensive knowledge, and have teacher competencies, namely; 1) Pedagogic competence, namely the ability to understand students, design and implement learning, assess learning outcomes, and develop students to realize their diverse potential. 2) Personality Competence, namely the individual's ability to reflect a stable, mature, wise and authoritative personality, be a role model for students and have noble character. 3) Social Competence, namely the ability of teachers to communicate and interact effectively with students, teaching staff, parents/guardians of students and the surrounding community. 4) Professional Competence, namely Mastery of the subject matter as a whole. This includes mastery of scientific content that covers the material and syllabus of school subjects, as well as mastery of scientific structure and methodology. Teacher competence is one of the factors that influence the achievement of learning and educational goals at Sekolah Sejahtera, but teacher competence does not stand alone, but is accompanied by 4 teacher competencies. Departing from this paradigm, this study aims to determine the pedagogic competence of teachers to improve the quality of education in the Prosperous School. This study uses a qualitative approach with in-depth interviews and documentation methods. The results showed that: (1) Pedagogical competence of teachers is one of the most important factors in improving the quality of education (2) Quality of learning for Sekolah Sejahtera Education is realized by the application of active, creative, and fun learning (3) Efforts by Principals in improving pedagogic competence teachers at Sekolah Sejahtera is to improve teacher competence through courses, webinars and learning media as well as managing the learning environment. (4) The efforts of the Prosperous School teachers in improving their pedagogic competence by participating in webinars and Teacher Working Groups. Keywords : Competence Pedagogic, improve the quality of education